Effectiveness and Safety of DOACs vs. Warfarin in Patients With Atrial Fibrillation and Frailty: A Systematic Review and Meta-Analysis - Zeng, Shan; Zheng, Yuxiang; Jiang, Jingzhou; Ma, Jianyong; Zhu, Wengen; Cai, Xingming (Frontiers in Cardiovascular Medicine, 2022)
Background Patients with atrial fibrillation (AF) and frailty are a considerable group in clinical practice. However, existing studies provide insufficient evidence of anticoagulation strategies for these patients. Therefore, we conducted a meta-analysis to determine the effectiveness and safety outcomes of direct oral anticoagulants (DOACs) for these patients. Methods Randomized controlled trials or observational studies reporting the data about the DOACs and warfarin therapy among frail AF patients were included. The search was performed in the PubMed and Embase databases up to March 2022. Frailty was defined using the most widely used claims-based frailty index or the cumulative deficit model-based frailty index. Results A total of 4 studies involving 835,520 patients were included. Compared with warfarin, DOACs therapy reduced the risks of stroke or systemic embolism (HR = 0.79, 95%CI: 0.69–0.90), ischemic stroke (HR = 0.79, 95%CI: 0.71–0.87), hemorrhagic stroke (HR = 0.52, 95%CI: 0.35–0.76), and all-cause death (HR = 0.90, 95%CI: 0.84–0.96). In safety outcomes, DOACs was significantly associated with reduced risks of major bleeding (HR = 0.79, 95%CI: 0.64–0.97) and intracranial hemorrhage (HR = 0.58, 95%CI: 0.52–0.65) compared to warfarin, but there were no statistically differences in gastrointestinal bleeding (HR = 0.97, 95%CI: 0.73–1.29). Conclusions DOACs exerted superior effectiveness and safety outcome than warfarin in AF patients with frailty.